Management Success Da'wah : Analysis Theoretical Monitoring and Evaluation - Anas Habibi Ritonga; Muhamad Rudi Wijaya (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2022)
Islam is a da'wah religion that must be socialized and transformed to the wider community in a wise and prudent way, love and compassion, polite and peaceful, democratic and persuasive so that they are safe, happy and prosperous both in this world and in the hereafter. In order for the da'wah carried out to run well, smoothly and successfully, good management is needed. Good management usually always applies management functions. Included among the management functions are monitoring and evaluation. Thus the monitoring and evaluation of da'wah plays an important role in the success of da'wah activities. And it is this activity (monitoring and evaluation of da'wah) that is carried out on Da'i that aims to achieve success in preaching. Design monitoring is carried out in 2 (two) ways, namely: (1) Monitoring through field visits , (2) Monitoring through progress reports obtained from reports from each unit in charge of the program whether it handles supporting programs/activities or the main leverage which includes the percentage of targets and realization of absorption of funds as well as the percentage of targets and realization of activity progress. While the evaluation design of da'wah evaluation can be done in two ways, namely evaluation of planning and evaluation of programs. Evaluation of the plan is carried out in order to find out whether the program carried out is in accordance with the vision and mission and objectives or not. While the evaluation of the program is carried out in order to find out whether the program being implemented is in accordance with the needs of the people or not.